Whole flaxseed, raw soybeans, and calcium salts of fatty acids supplementation for transition cows: follicle development and embryo quality. Issue 4 (2nd October 2017) - Gandra, Jefferson Rodrigues; Verdurico, Lenita Camargo; Mingoti, Rodolfo Daniel; Takiya, Caio Seiti; Gardinal, Rodrigo; Vendramini, Thiago Henrique Aniballe; Barletta, Rafael Villela; Visintin, José Antonio; Rennó, Francisco Palma
Abstract: The objective of this study was to evaluate the effects of diets rich in omega-3 and -6 fatty acids (FA) during the transition period and early lactation on size and number of follicles, oocyte and embryo quality, and blood metabolites of Holstein cows. Forty-two cows were assigned to the diets: control (CON, with no fat sources and dietary ether extract content of 28.8 and 24.8 g/kg during the pre- and post-partum periods, respectively); whole flaxseed (WF, diet rich in omega-3 FA), 60 and 80 g/kg of WF during the pre and post-partum periods, respectively; whole raw soybeans (WS, diet rich in omega-6 FA), 120 and 160 g/kg of WS during the pre and post-partum periods; and calcium salts of unsaturated fatty acids (CSFA, diet rich in omega-6 FA), 24 and 32 g/kg of CSFA during the pre and post-partum periods. Diets were supplied from 35 d of the expected calving date until 84 days in milk (DIM). The ovaries of cows were examined from 14 to 84 DIM. Ovum pick-ups were performed on days 35 ± 7 and 65 ± 7 of lactation. Diets rich in omega-3 and -6 FA had greater follicle number than the CON. No differences were detected among diets rich in omega-3 and omega-6 FA on number and size of follicles and corpus luteum area. Cows had similar oocyte quality regardless of diet supplied. Although FA supplementation had no effect on embryo quality (number of cleaved and viable embryos), diets rich in omega-6 FA had lower viable embryos compared with WF. Supplementation with diets rich in omega-3 and -6 FA resulted in greater blood cholesterol concentration in early lactation cows. Fat supplementation increased the number of small and total follicles of early lactating cows. However, diets rich in omega-3 or -6 FA had no effect on oocyte quality. Cows fed WS during the transition period had the least viable embryos, and consequently cows fed diets rich in omega-6 FA had lower viable embryos than those fed WF.